2020
DOI: 10.31083/j.jin.2020.01.1226
|View full text |Cite
|
Sign up to set email alerts
|

Herbal complex ‘Buyang Huanwu Tang’ improves motor endplate function of denervated-dependent skeletal muscle atrophy in rat

Abstract: Denervated-dependent skeletal muscle atrophy is a disease induced by skeletal muscle associated peripheral neuro-disconnection. Its specific molecular mechanisms remain unknown. The treating for denervated-dependent skeletal muscle atrophy is applied with an herbal complex Buyang Huanwu Tang used in traditional Chinese medicine and subjected to the established denervated-dependent skeletal muscle atrophy in rat models, and the therapeutic effects and associated mechanisms were evaluated in the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Furthermore, BYHWT treatment is also associated with decreased levels of skeletal muscle atrophy-specific molecules MAFbx and MuRF1. This finding aligns with the outcomes of inflammatory response and motor endplate alterations following BYHWT treatment (Zhou et al, 2020). NeuroHeal, a new neuroprotective drug for peripheral nerve injury, discovered using artificial intelligence is based on a combination of two approved drugs, acamprosate and ribavirin, which facilitate its preparation for clinical application.…”
Section: Regulation Of Ubiquitin-proteasome and Autophagy-lysosome Pa...supporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, BYHWT treatment is also associated with decreased levels of skeletal muscle atrophy-specific molecules MAFbx and MuRF1. This finding aligns with the outcomes of inflammatory response and motor endplate alterations following BYHWT treatment (Zhou et al, 2020). NeuroHeal, a new neuroprotective drug for peripheral nerve injury, discovered using artificial intelligence is based on a combination of two approved drugs, acamprosate and ribavirin, which facilitate its preparation for clinical application.…”
Section: Regulation Of Ubiquitin-proteasome and Autophagy-lysosome Pa...supporting
confidence: 73%
“…The enhanced cross-sectional area was substantiated by diminished levels of TNF-α in the gastrocnemius and IL-6 in the soleus muscle (Choi et al, 2018). Buyang Huangwu Tang (BYHWT), a classic Chinese medicine formula, ameliorated the inflammatory response in denervation-dependent skeletal muscle atrophy rat models (Zhou et al, 2020). Wu et al (2019) found that negative regulation of pro-inflammatory cytokine mediated by salidroside attenuates denervation-induced skeletal muscle atrophy.…”
Section: Inhibition Of Pro-inflammatory Factorsmentioning
confidence: 99%